Analytic hierarchy process based methods and its applications - Mohd. Lazim Abdullah (Penerbit Universiti Malaysia Terengganu, 2015)
Plentry of problems faced by the decision makers today are the result of insufficient decision making tools. The inappropriate of procedures finally leads to inconsistency and vagueness of the choices made. In order to understand the problems better and make a good decision, appropriate analysis tools are required. Some of these tools are presented in this book. They are based on a number of different mathematical and computational approaches.